2022
DOI: 10.1038/s41391-022-00559-w
|View full text |Cite
|
Sign up to set email alerts
|

Low quality of life in men with chronic prostatitis-like symptoms

Abstract: Background Chronic prostatitis (CP) can impair health-related quality of life (QOL), but the full impact of CP, including the impact of CP-like symptoms in men who have no CP diagnosis (CPS), is unknown. We estimated the impact of diagnosed CP (DCP) and CPS on Health-related QOL. Methods From a representative nationwide survey of men aged 20–84 in Japan, we determined the prevalence of DCP and also of CPS. For CPS, we used Nickel’s criteria, which were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The survey was designed to represent the general population of Japan based on quota sampling from the national census in 2015 using quota sampling [ 12 ] and continued until the target of 5,000 men was reached at each stratum. The survey details and the target population’s characteristics are described elsewhere [ 3 ]. This study was conducted in accordance with the World Medical Association’s Declaration of Helsinki [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey was designed to represent the general population of Japan based on quota sampling from the national census in 2015 using quota sampling [ 12 ] and continued until the target of 5,000 men was reached at each stratum. The survey details and the target population’s characteristics are described elsewhere [ 3 ]. This study was conducted in accordance with the World Medical Association’s Declaration of Helsinki [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Chronic prostatitis/chronic pelvic pain syndrome (CP), grouped as category III in the National Institutes of Health (NIH) classification, is a common disease in men, with an estimated prevalence of 1.8–9.7% of the male population [ 1 , 2 ]. CP significantly impairs the quality of life (QOL) and is widely distributed among older adults and young people, who play a central role in economic activities [ 3 ]. Therefore, CP is a disease that significantly impacts society [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their recent study, Bai et al found a higher incidence of depression, anxiety, somatization disorder, and obsessive-compulsive behavior in patients with ED associated with CP/CPPS (40). The literature is quite scarce regarding the incidence of anxiety and depression in patients with CP/CPSS; however, in the few studies analyzed, the incidence of anxiety symptoms in patients with CP/CPPS was found in about 60-90% of cases (41,42), while with respect to the incidence of depressive symptoms, these were found to be present in approximately 27-90% of cases in patients with CP/CPPS (42)(43)(44). This study aims to investigate a possible relationship between CP and PD and to characterize the psychological profile of patients suffering from PD, with or without concomitant CP.…”
Section: Psychological Consequences Of Pd and Cpmentioning
confidence: 99%
“…In the early years of the 20th century, migration from gonococcal urethritis accounted for 80% of prostatic abscesses, 25,26 but widespread antimicrobial treatments have reduced the frequency of prostate abscesses. Currently, prostate abscesses are rare, accounting for 0.5%–2.5% of all diseases of the prostate or 0.2% of all diseases of the genitourinary system 27 .…”
Section: Four Harmful Effects Of Not Recognizing Prostatitismentioning
confidence: 99%